Participação da via canônica WNT no efeito protetor do metotrexato em ratos com artrite na articulação temporomandibular e análise comparativa à artrite em joelho - Costa, Ana Carolina de Figueiredo (2023)
Rheumatoid arthritis (RA) is an autoimmune disease that affects synovial joints and methotrexate (MX) is considered the first-line treatment. The first chapter of this thesis evaluated the effects of MX on nociception, joint damage, canonical Wnt pathway and glial cells in the trigeminal nociceptive pathway (TNP) of rats with RA in the temporomandibular joint (TMJ). The animals were divided into groups (n=6): Control, RA and RA+MX. RA induction occurred by administration of complete/incomplete Freund's adjuvant and methylated bovine serum albumin (mBSA), followed by three intra-articular injections of mBSA (1x/week). The animals were treated with MX (0.75 mg; 2x/week) for 15 days and euthanized 24 hours after the third injection. Mechanical hyperalgesia, inflammatory parameters in the TMJ, analysis of facial expressions, immunoexpression of c-Fos, Wnt-10b, β-catenin, glutamine synthetase (GS), Iba-1 and microglial morphology in the TNP were evaluated. Arthritic animals showed a significant increase in mechanical hyperalgesia and facial expression scores, intense inflammatory infiltrate in the synovial membrane (SM), degeneration and depletion of proteoglycans in the articular cartilage (AC). Furthermore, there was a significant increase in the immunoexpression of TNF-α, IL-17 in MS and AC, while IL-10 showed a significant increase only in SM. MX reversed all parameters related to nociception, inflammation and joint damage. RA induction promoted an increase in the immunoexpression of c-Fos, Wnt-10b, β-catenin and GS in the trigeminal ganglion (TG) and an increase in the immunoexpression of c-Fos and Iba-1 in the subnucleus caudalis of the trigeminal (Sp5C), as well such as, increased total length and number of microglia branches. MX significantly reduced the immunoexpression of these markers. It is concluded that MX reduces nociceptive behavior, joint damage, number of glial cells in the TNP and immunoexpression of the Wnt/β-catenin pathway in the TG. The second chapter showed a comparative study of the development of RA in the TMJ and knee (K) of rats, which were divided into groups (n=6): TMJ/Control, TMJ/RA-24h, TMJ/RA-7D, K/Control, K/RA-24h and K/RA-7D. Euthanasia occurred 24 hours or 7 days after the third mBSA injection. Mechanical hyperalgesia, cellular influx into synovial fluid, histopathological changes, immunoexpression of metalloproteinase (MMP)-9 and birefringence of collagen fibers in the TMJ and K cartilage were evaluated. There was a reduction in the nociceptive threshold of arthritic animals in both joints and periods of euthanasia. In the TMJ and K, there was a significant increase in cellular influx into the synovial fluid 24 hours after the third injection and in the K/RA-7D group. The TMJ/RA-24h and K/RA-24h groups showed edema, intense inflammatory infiltrate in the SM, hypertrophic chondrocytes, reduced metachromasia, increased MMP-9, reduced total collagen fibers and type I collagen, and increased collagen fibers. type III in AC. In the TMJ/RA-7D group, there was a reduction in these parameters, a fact not observed in the K/RA-7D group. Thus, the nociceptive response is similar in both joints in the acute and chronic phases of RA, however, there is an improvement in joint damage in the TMJ in the chronic phase, suggesting tissue repair.